PENAPISAN BAKTERI PENGIKATSENG (Zn) DAN TEMBAGA (Cu) DARI KOLONGPASCA PENAMBANGAN TIMAH - SUSANTI I; E PRATIWI; C FEBRIYANTI; H HELMI; R.K. FEMBRIYANTO (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2012)
Bangka Island is one of the biggest tin mine source land. Tin mining activities in Bangka Island made some environmental problems. The impact of tin mining are some critical areas, Acid Mine Drainage (AMD) and mine pit ponds in Bangka Island. The purposes of the research were to isolate and to screenzink-accumulating and copper-accumulating bacteria, and to identify the bacteria from post tin-mining pit ponds. Sampling was conducted in two locations (stations) in Rebo Village,from 0 and 5 years old post tin-miningpond aged. The sampling used purposive random sampling method. The research measured three parameters: the level of Zn and Cu concentrationsdecreasing, dry weight cell of bacteria, the number of bacteria cell, and pH changing of medium. Research has resulted 40 isolates from 17 genera. Stomacoccus sp. has the highest Zn leveluptake (11.07 ppm or 32.56%) and it has the highest dry weight cells (4.8 mg). The bestCu-accumulatingbacteria was shown by Serratia sp. Serratia sp could accumulate 25,2 ppm or up to 70,99% Cu. The observation showed that Serratia sp. had the highest cell biomass (13,87 mg). The bacteria which could accumulate 2 kind of heavy metal Zn and Cu wereAcetothermus sp. (7.86 ppm Zn and 7.7 ppm Cu); Sarcina sp. (10.63 ppm Zn and 7.1 ppm Cu); andSacharococcus sp (3.84 ppm Zn and 11.8 ppm Cu). These bacteria have potential to decrease both of heavy metal kinds: Zn and Cu from post tin-mining pit ponds.